Challenges in the path of Retail Industry - Begum, Hassina (International Journal of Scientific Research and Management (IJSRM), 2015)
The paper provides the detailed information about the various challenges, which acts as a hurdle in the path of retail industry. Retail industry builds a strong linkage with world economy. Retailer is the first contact point who gets face-to-face interaction with the customer so that to satisfy its needs. The challenges faced by the retail industry are financial, Technological, Ethical and environmental. As the market is growing government policies are becoming more favorable, emerging technology also helps in the upliftment of retail industry. Due to the introduction of FDI various global giants gets chance to enter into the Indian retail sector, which leads to the reduction in the profit of Indian retail industry. Government is also not recognizing the retail industry, which becomes a challenge in the path of retail sector. Incapability of manager, location of the shop, lack of infrastructure, supply chain inefficiency unavailability of latest technology, sudden failure in the hardware and software gives a back stack to retail industry. As far its seen that the consumption of the energy is rising day by day. Retailers should be socially responsible so that face these challenges.